Construction logistics: a simulation case study to improve performance processes. (8th February 2022) - Jaafar, Kamal
This paper, focuses on details about pre-cast construction logistics management. Specifically, the management of the precast stockyard layout in precast concrete products industry. Designing an effective precast stockyard with effective storage and structural precast element retrieval is a complex process. The paper will discuss how to ensure efficient storage, precast elements dispatch, ease of rotation of precast elements within precast stockyard, and a smooth precast element retrieval process from any stockyard. In addition, the paper will show how effective stockyard layout can reduce the dispatch time, loading time, and queuing time of the precast elements within the stockyard. Finally, the paper will include simulation modelling using 'ARENA' software to optimize, design, and test the new stockyard layout that we established and compare it with the current status of the precast stockyard. A 'what if' analysis will be implemented from the simulation model in order to cover various stockyard conditions.